2005
DOI: 10.1063/1.1940131
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nitrogen growth pressure on the ferromagnetic properties of Cr-doped AlN thin films

Abstract: We report the magnetic properties of Cr-doped AlN thin films grown by reactive magnetron sputtering under various nitrogen pressures. Ferromagnetism is observed up to the highest temperature measured, 400 K, and shows strong dependence on the Cr concentration and, especially, the nitrogen growth pressure. By varying the nitrogen pressure during film growth, the magnetic properties of the films can be changed while keeping a constant Cr concentration. The ferromagnetism is enhanced in the films that were grown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
40
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 28 publications
8
40
0
Order By: Relevance
“…A recent calculation by Liu et al and Li et al indicated the introduction of nitride (N) vacancy is beneficial to stabilize the ferromagnetic configuration and enhance the ferromagnetism in Cr-doped GaN and AlN [35,36]. Ferromagnetism due to create N vacancy was also reported in Cr and Cu-doped AlN films [12,37]. Based on PL and SQUID measurements, in our study, magnetic properties of Si-doped AlN films were improved when large-scale defects appeared in AlN lattice.…”
Section: Magnetic Property Analysismentioning
confidence: 91%
“…A recent calculation by Liu et al and Li et al indicated the introduction of nitride (N) vacancy is beneficial to stabilize the ferromagnetic configuration and enhance the ferromagnetism in Cr-doped GaN and AlN [35,36]. Ferromagnetism due to create N vacancy was also reported in Cr and Cu-doped AlN films [12,37]. Based on PL and SQUID measurements, in our study, magnetic properties of Si-doped AlN films were improved when large-scale defects appeared in AlN lattice.…”
Section: Magnetic Property Analysismentioning
confidence: 91%
“…There have been many reports on roomtemperature ferromagnetism for wide bandgap semiconductor doped with a few percent of 3d transition-metal ions. The host materials for the DMS have been ZnO [1,[4][5][6], ZnS [2,[7][8][9][10][11][12], TiO 2 [13,14], SnO 2 [15,16], GaAs [17], AlN [18], and GaN [19]. TM-doped DMS materials always suffer from problems such as formation of secondary phase and/or clusters [2].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16] In particular, Crdoped AlN is one of the most promising materials for practical applications in spin-dependent electronic devices because its Curie temperature has been reported to be above 900 K, which is the highest among III-nitrides. 8,[10][11][12][14][15][16] In the previous reports, the room-temperature ferromagnetism was observed in Cr-doped AlN films fabricated at various substrate temperatures by sputtering 10,15,16) and molecular beam epitaxy, 8,11,12,14) but their magnetic moments were different from each other. In our previous paper, it was reported that the room-temperature ferromagnetism cannot be observed in Cr-doped AlN film with the Cr concentration of 0.07 fabricated at room temperature on a thermally oxidized Si (001) substrate by reactive dc magnetron sputtering.…”
Section: Introductionmentioning
confidence: 99%